Marker layer technology: advanced crack detection in elastomeric bearings - Halladay, J.R. (My University, 2015)
Helicopter elastomeric bearings are typically replaced "on condition", that is, once elastomer fatigue degradation has reached a prescribed depth, the bearings are removed from service. To simplify inspection and enable proactive maintenance, LORD Corporation has developed marker layer technology using a contrasting color elastomer to visually indicate that a bearing is approaching the end of its service life.
Keywords: Structures & Materials